Uncommon Solid Pancreatic Neoplasm: The Role of New Modalities of Ultrasound Endoscopy - Cátia Leitão; Helena Ribeiro; João Pinto; Ana Caldeira; Eduardo Pereira; António Banhudo (GE: Portuguese Journal of Gastroenterology, 2017)
Undifferentiated carcinoma with osteoclast-like cells is a rare pancreatic neoplasm with unique ultrasound endoscopic features. A 59-year-old female presented with a 3-month history of weight loss. Abdominal computed tomography and endoscopic ultrasound showed a large pancreatic tumor with a heterogeneous echotexture and liver metastasis. Endoscopic ultrasound fine needle aspiration was used to establish the diagnosis. In this case report, we review the endoscopic, clinical, and pathological features of this type of tumor and describe for the first time the endoscopic features of real-time elastography and contrast enhancement. Real-time elastography revealed a heterogeneous predominantly blue pattern suggestive of pancreatic malignancy, and the contrast-enhanced endosonography showed a hypervascular mass and distinctive vascular (solid) and avascular (liquid/necrotic) components of the lesion, guiding the fine needle aspiration.